Relationship Between Motivation And Personal Development - Uktamova, Mokhigul; Odilova, Sarvinoz (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article scientifically analyzes the relationship between motivation and personal development. The study examines the impact of internal and external motivation on a person's goal-oriented activity, level of self-awareness, and personal and professional growth. The article, based on the analysis of theoretical sources, questionnaire results, and practical examples, highlights the role of motivation as an important factor in the process of personal development. The results of the study show that by increasing motivation, a person can fully realize his potential and increase his effectiveness in achieving life goals.